Study on the wellbore flow and phase transition during formation H2S invasion. (1st January 2013) - Dou, Liangbin; Li, Gensheng; Shen, Zhonghou; Huang, Zhongwei; Song, Xianzhi
Considering the special physical properties of hydrogen sulphide (H2 S) and its phase transition in the wellbore, a mathematical model for wellbore flow and heat transfer during formation H2 S invasion was established. Heat transfer and pressure were calculated along with H2 S physical properties parameters, and a solution method of the model was proposed. The results indicate that liquid H2 S transforms into gas state during its rising process in the annulus when choke pressure is low; the flow above phase transition point is two-phase flow while the flow below phase transition point is single-phase flow in the annulus. The paper exhibits the results and the reasons of the bottom-hole pressure and the depth of phase transition varying with different H2 S influx rate, injection rate, choke pressure, and land surface temperature. The study is of certain significance for improving the safety during the exploration of acidic oil and gas reservoirs.